The Influence of Big-Book Learning Media Based on Scientific Literacy on Students' Scientific Reading Ability: Text Scaffolding Skills and Reading Comprehension (Universitas Pendidikan Indonesia, 2024)
Choosing the right learning media is needed to improve 21st-century knowledge and skills, such as scientific reading skills. Big-Book is a learning medium in the form of a book that is relatively large in size and contains picture illustrations and text. This research aims to determine the implementation and influence of scientific literacy-based big-book learning media on students' scientific reading abilities. The method used in this research is Quasi-Experimental. The subjects used in this research were class VII students, junior high school using 2 classes consisting of 30 students. Sampling was carried out using purposive sampling, namely taking samples with certain considerations. The data collection technique in this research is a test by conducting a pretest and posttest. Meanwhile, the data analysis technique used is the ANCOVA analysis test. The research results based on the ANCOVA test show a significance value of 0.00 - 0.05, meaning that big-book learning media based on scientific literacy has a significant difference or influence on students' scientific reading abilities. So this research concludes that big-book media based on scientific literacy is very suitable to be used as a support for special learning regarding scientific reading skills.